Siber Gözetim: Toplumsal Denetim Aracı Olarak İnternetin Dönüşümü - Karslıoğlu, Fidan (İstanbul Bilgi Üniversitesi, 2014)
Freedom of expression plays an important role in construction and maintenance of a pluralistic democratic society order. The most effective enjoyment of the freedom of expression in today’s world is attained through the use of mass media. The mass media is widely invoked to access to information, news, ideas and so on.. It can be used as an important tool in formation of public opinion. In this respect, the freedom of expression constitutes the core of the freedom of mass media. Hence, regulations having an impact on the freedom of expression influences the freedom of mass media as well. However due to the nature of mass media, it may be subject to some other specific legal rules in addition to those pertaining to the freedom of expression. In order to grasp the scope of and the limitation to the freedom of expression and mass media, there is a clear need to examine the relevant legal corpus of law. This thesis – adopting the view that freedom of expression encompasses also the freedom of mass media- begins with conducting a theoretical inquiry on the concept of the freedom of expression. Secondly, the analysis turns to the role of freedom of mass media in enjoyment of the freedom of expression and the effects of the notion of monopolisation on such a role. Finally the regulations of the European Convention on Human Rights and 1982 Constitution of Turkey concerning the freedom of expression and mass media are discussed. This discussion compares and contrasts the scope and limits of the freedom of expression and mass media set out in these texts in light of a survey of the jurisprudence of the European Court of Human Rights and the Constitutional Court of Turkey.

In comparison to previous centuries, technology manifests itself in the daily lives of people in the 21st century in dramatically different ways. Technology has become a substantial part of daily life. Privacy issues have arisen because of people being online and accessible at any time, and this has resulted in violations of privacy. In the previously mentiond case, government violated privacy, resulting in negative outcomes. Those in government have taken a keen interest in observing the practices of people online. Governments have been motivated to foster societies that are obedient to their rules. As such, governments continuously monitor new currents in technological thought and social formations to watch for opposition groups or technologies that may erode their power.
Cyber Curveillance: The Transformation of the Internet into a Tool of Social Governance